Fatwa, Marketing, and Halal Certification: A Socio-Legal Analysis of The Indonesian Ulama Council Fatwa Number 80 of 2022 - Alanazi, Meshal Saleh A.; Meriyati; Hidayat, Syahrul Ramadhan; Alyusufi, Abdulhaleem Obaid A. (International Journal of Law and Society, 2024)
This study examines the impact of Indonesian Ulema Council (MUI) Fatwa Number 80 of 2022 on consumer interest in halal-certified products among Micro, Small, and Medium Enterprises (MSMEs), specifically pempek at 26 Ilir Market in Palembang. The research employs a qualitative socio-legal approach, utilizing interviews, field observations, and document analysis. The findings indicate that halal certification influences consumer purchasing decisions, as products with a halal label are perceived as more trustworthy and compliant with Islamic business ethics. However, MSMEs face challenges such as certification costs, lack of awareness, and regulatory complexity. The study concludes that integrating fatwa-based regulations with legal frameworks for halal product assurance plays a crucial role in shaping consumer preferences and strengthening the halal market ecosystem. Strengthening halal certification policies and socialization efforts is essential for enhancing MSME competitiveness in Indonesia's halal industry.